Urgensi Syarat Penanaman Nilai-Nilai Religius di Sekolah Sebagai Basis Pengembangan Kecerdasan Spiritual Peserta Didik di SMAN 1 Srengat Blitar - Aisyatur Ridlo Al Baidlo’; Siti Khoirun Nisak (Mathematics Education Study Program, 2025)
The inculcation of religious values ​​in schools is highly urgent in shaping character and developing students' spiritual intelligence. This study aims to examine the requirements that must be met in instilling religious values ​​in schools and their implications for the development of students' spiritual intelligence at SMAN 1 Srengat Blitar. This study uses a qualitative case study approach with data collection techniques through observation, interviews, and documentation. The results show that the requirements for instilling religious values ​​applied at SMAN 1 Srengat are in accordance with the goals of national education and school objectives, active participation from all school members, an environment and facilities that support the instillation of religious values ​​in schools, religious activities that are carried out routinely every day, and certain penalties for students who do not implement religious values ​​at school. Fulfilling these requirements has been proven to strengthen students' spiritual intelligence, which is reflected in increased awareness of worship, attitudes of tolerance, honesty, and social responsibility. Thus, instilling religious values ​​in schools is not only a moral necessity, but also an important basis for building students' spiritual intelligence as a whole.